COP28 COMMITMENT AND IMPLEMENTATION IN PROMOTING SUSTAINABLE FOOD SYSTEM TRANSFORMATION - Almirah Nahda Ayu Wibiksono; Nezwa Nabilaysca Aura ris; Nazwa Farasyah Nazwa; Dwi Ardiyanti Dwi (Proceedings International Indonesia Conference on Interdisciplinary Studies, 2025)
Referring to the United Nations Climate Change Conference (COP28), which is a crucial point in global efforts to address the impact of climate change on the food system. Climate change is considered to have disrupted food productivity and worsened global food security, while the agricultural sector is one of the main contributors to carbon emissions. This study aims to examine the potential of COP28 to bridge the commitments of this international forum as a concrete implementation toward a sustainable food system. The hypothesis proposed states that COP28 can drive the transformation of the global food system through evidence-based policies, cross-sectoral collaboration, and technological innovation. The method used is a quantitative approach with data collection techniques data collection including questionnaires, to evaluate public perceptions. The results indicate that COP28 is perceived as having outcomes that can strengthen synergy among stakeholders, promote the adoption of environmentally friendly technologies, and reinforce policy frameworks to support climate action in the food sector. These findings emphasize the importance of concrete actions and of initiatives resulting from the conference. Thus, COP28 is not only an international discussion forum but also a concrete step toward systemic change toward food security and global carbon emission reduction.